Home-Based HIIT and Traditional MICT Prescriptions Improve Cardiorespiratory Fitness to a Similar Extent Within an Exercise Referral Scheme for At-Risk Individuals - Hesketh, Katie; Jones, Helen; Kinnafick, Florence; Shepherd, Sam O.; Wagenmakers, Anton J. M.; Strauss, Juliette A.; Cocks, Matthew (Frontiers in Physiology, 2021)
Exercise referral schemes (ERS) are used to promote physical activity within primary care. Traditionally, ERS are conducted in a gym or leisure-center setting, with exercise prescriptions based on moderate-intensity continuous training (MICT). Home-based high-intensity interval training (Home-HIIT) has the potential to reduce perceived barriers to exercise, including lack of time and access to facilities, compared to traditional MICT prescription used with ERS and improve health related outcomes. We hypothesized that Home-HIIT would mediate greater improvement in cardiorespiratory fitness (CRF) by virtue of greater adherence and compliance to the exercise prescription, compared to MICT. Methods: Patients enrolled on an ERS (Liverpool, United Kingdom) were recruited for a pragmatic trial. Participants self-selected either 12 weeks of MICT (45–135 min/week at 50–70% HRmax) or Home-HIIT (4–9 min × 1 min intervals at ≥80% of HRmax, interspersed with 1 min rest). The primary outcome was the change in CRF (VO2peak) at post-intervention (12 weeks) and follow-up (3-month post intervention), using intention-to-treat analysis. Results: 154 participants (age 48 ± 10y; BMI 30.5 ± 6.1 kg/m2) were recruited between October 2017 and March 2019, 87 (56%) participants chose Home-HIIT and 67 (44%) MICT. VO2peak increased post-intervention in both groups (MICT 3.9 ± 6.0 ml.kg–1.min–1, Home-HIIT 2.8 ± 4.5 ml.kg–1.min–1, P < 0.001), and was maintained at follow-up (P < 0.001). Fat mass was only reduced post MICT (MICT −1.5 ± 6.3 kg, P < 0.05, Home-HIIT −0.2 ± 2.0 kg, P = 1.00), but the reduction was not maintained at follow-up (MICT −0.6 ± 5.1 kg, Home-HIIT 0.0 ± 2.2 kg, P > 0.05). Adherence to the prescribed programs was similar (MICT 48 ± 35%, Home-HIIT 39 ± 36%, P = 0.77). Conclusion: This is the first study to evaluate the use of Home-HIIT for individuals in a primary care setting. Contrary to our hypothesis, adherence to both exercise prescriptions was poor, and CRF improved to a similar extent in both groups with improvements maintained at 3-month follow-up. We provide evidence that, although not superior, Home-HIIT could be an effective and popular additional exercise choice for patients within primary care based ERS. Clinical Trial Registration: [ClinicalTrials.gov], identifier [NCT04553614].